Effects of Lorentz symmetry breaking by a tensor field subject to Coulomb-type potential on relativistic quantum oscillator - Ahmed, Faizuddin (Proceedings of the Royal Society. A, Mathematical, physical, and engineering sciences, 2022)
In this paper, we solve the Klein–Gordon oscillator analytically under Lorentz-violating effects defined by a tensor field subject to a Coulomb-type scalar potential. We obtain the bound-state solutions of the quantum system by choosing various electromagnetic field configurations and discuss the effects on the energy profiles and the wave function of these oscillator fields.